2021
DOI: 10.31349/revmexfis.67.365
|View full text |Cite
|
Sign up to set email alerts
|

Temperature profiles due to continuous hot water injection into homogeneous fluid-saturated porous media through a line source

Abstract: We report a theoretical study to determine the temperature profiles due to the continuous andconstant injection of hot water through a line source, into a homogeneous fluid-saturated porous medium which has had initially a constant temperature T∞. In our treatment we have taken in to account the simultaneous injection of constant fluxes of volume fluid, q, and of heat, φ. By using a far-field description, we found similarity solutions for the dimensionless temperature depending on the Peclet number, P e, as the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Now, the exponents of the power law r f /H ∼ t n are n = 0.51 ± 0.02 if θ = 0 and n = 0.46 ± 0.02 if θ = π/2. These exponents indicate, as can be seen in Figure 8, that the initial fronts were nearly circular and behaved approximately according to the power law for hot water radial injection [28]. Following the study of the thermalization of the preformed circular steam chamber, we provide four thermographies for the indicated time instants in Figure 10.…”
Section: Transient Steam Flow In a Circular Steam Chambermentioning
confidence: 93%
See 1 more Smart Citation
“…Now, the exponents of the power law r f /H ∼ t n are n = 0.51 ± 0.02 if θ = 0 and n = 0.46 ± 0.02 if θ = π/2. These exponents indicate, as can be seen in Figure 8, that the initial fronts were nearly circular and behaved approximately according to the power law for hot water radial injection [28]. Following the study of the thermalization of the preformed circular steam chamber, we provide four thermographies for the indicated time instants in Figure 10.…”
Section: Transient Steam Flow In a Circular Steam Chambermentioning
confidence: 93%
“…Moreover, in the same figure, it is observed that the rate of change of r f (θ = 0)/H was larger than r f (θ = π/2)/H, due to the influence of the buoyancy of steam. In contrast, when a hot liquid is injected radially into a similar geometry at a constant flow rate, q, the Darcy velocity of the front close to the injection pipe, v r , evolves as v r = dr f /dt = q/2πr f , which yields that r f /H ∼ t 0.5 [28]. In addition, the time-dependent temperature distributions in the preformed steam chamber during the steam injection (see Figure 6) were obtained using an infrared camera: model FLIR SC660, which had a high performance infrared system within the long-wave spectral range: 7.5-13 µm.…”
Section: Transient Steam Flow In An Elliptical Steam Chambermentioning
confidence: 99%